Application and development of nanomaterials in the diagnosis and treatment of esophageal cancer - Xiao, Qianwen; Zhang, Yafei; Zhao, Anshun; Duan, Zhikang; Yao, Jun (Frontiers in Bioengineering and Biotechnology, 2023)
Esophageal cancer is a malignant tumor with a high incidence worldwide. Currently, there are a lack of effective early diagnosis and treatment methods for esophageal cancer. However, delivery systems based on nanoparticles (NPs) have shown ideal efficacy in real-time imaging and chemotherapy, radiotherapy, gene therapy, and phototherapy for tumors, which has led to their recent widespread design as novel treatment strategies. Compared to traditional drugs, nanomedicine has unique advantages, including strong targeting ability, high bioavailability, and minimal side effects. This article provides an overview of the application of NPs in the diagnosis and treatment of esophageal cancer and provides a reference for future research.